Optimization of Feed-in Tariff mechanism for residential and industrial photovoltaic adoption in Hong Kong. (20th June 2023) - Zhang, Ruixiaoxiao; Lee, Minhyun
Abstract: Due to the late introduction of Feed-in Tariff (FiT) Scheme to Hong Kong's context, its effectiveness, efficiency, and optimization have merely been investigated yet. Therefore, this study proposes two FiT mechanisms according to the policy characteristics and structure elucidated from existing literatures (i.e., payoff, tariff, and contract structures) (i) Mechanism 1 (i.e., M1): follows the current policy characteristics with a short-term contract structure, which terminates in 2033; and (ii) Mechanism 2 (i.e., M2) introduced a widely adopted policy characteristic with a long-term contract structure, which allows to sell all electricity generated to the power grid. The proposed FiT rate under M1 and M2 guarantees the profitability of the solar photovoltaic (PV) installers with different scales. For residential PV installers (i.e., small-scale PV systems with installed capacity less than10 kW), 6–10 years of discounted payback period (DPB) is considered as the optimization objective. As for industrial PV installers (i.e., large-scale PV systems with installed capacity of 200–1000 kW), 8–12% of internal rate of return (IRR) is considered as the optimization objective. Results indicate that the current FiT rate is slightly high for residential PV installers, and it is recommended to be lowered after 2024 to fit the proposed FiT range, and then levered up in 2028 to ensure the profitability of late participation under M1. Meanwhile, the current FiT rate is found significantly low for industrial PV installers, and it is suggested to be levered up to the proposed FiT range. Furthermore, policy reform is highly recommended altering from M1 to M2 when current policy expires (i.e., 2033). In terms of the techno-economic analysis based on the calculation of levelized profit of electricity (LPOE) where self-consumption of PV system-generated electricity is considered as energy bill savings under M1, the long-term profitability for industrial PV installers under M1 is found to be higher than M2, whereas the opposite is observed for residential PV installers. The contribution of this study is attributed to the flexibility and applicability of the optimized results, the context-specific investigation of the market-independent renewable energy development, and the comprehensive parameters considered in the model development. The results of this study are believed to shed light on policy implications, grid parity, and investment recommendations for the government, utility companies, and PV installers in the long run. Graphical abstract: Image 1 Highlights: Payoff, tariff, and contract structures regarding FiT Scheme are reviewed. FiT rates were optimized under current (M1) and improved (M2) FiT mechanisms. DPB and IRR are considered for residential and industrial PV installers. Results have shed light on policy implications regarding current FiT rates. Policy reform is suggested according to economic analysis in a long run.